The Islamic worldview Islamic jurisprudence :an American Muslim perspective - al-Hibri, Azizah 1943- (Islamic jurisprudence (American Bar Association), 2015)
With Qur'anic textual analysis and commentary, this book provides both the Muslim and non-Muslim reader with a basic understanding of the legal foundations of Islam. It introduces the sources of Islamic law and their significance in the hierarchy of Islamic jurisprudence while presenting Dr. al-Hibri's articulation of the Islamic worldview. The Islamic Worldview introduces the Qur'an as the supreme source of Islamic law and discusses basic rules and principles that have been noted by jurists over time in understanding and interpreting it, and how these rules can and have been applied toward the evolution of a uniquely Islamic global perspective